The prevalence and determinants of unhealthy feeding practices among children 6-23 months of age in Burkina Faso - Lanou, Bienou Hermann; Savadogo, Boubacar; Diendiere, Jeoffray; Zeba, Augustin N (World Nutrition, 2025)
BackgroundUnhealthy food consumption in early childhood is an emerging concern in low- and middle-income countries, including Burkina Faso. Poor dietary quality during the complementary feeding period may increase the risk of both undernutrition and diet-related non-communicable diseases. However, evidence from nationally representative surveys on the specific drivers of this phenomenon in the Sahel region of West Africa remains limited.ObjectiveThis study aimed to address this gap by investigating the prevalence and associated factors of unhealthy feeding practices among children aged 6 to 23 months in Burkina Faso using recent national dataMethodsData from the Burkina Faso Demographic and Health Survey (DHS) were analyzed. Survey-weighted logistic regression models were used to identify factors associated with unhealthy feeding practices.ResultsOverall, 63.1% of children in this age group had at least one unhealthy feeding practice (UPF). Factors associated with higher odds of UPF included urban residence and frequent household media exposure. Also included were the following counterintuitive findings: younger child age, greater maternal dietary diversity, and multiple antenatal care visits.ConclusionsUPF among young children in Burkina Faso is not only widespread but also influenced by a complex interplay of maternal and household characteristics. This study provides novel insights indicating that interventions must go beyond basic awareness to promote context-specific infant and child feeding practices, even in more advantaged households.